A strategy for preparing high-efficiency and economical catalytic electrodes toward overall water splitting. Issue 24 (16th June 2021) - Yao, Dongxue; Gu, Lingling; Zuo, Bin; Weng, Shuo; Deng, Shengwei; Hao, Weiju
Abstract : Electrolyzing water technology to prepare high-purity hydrogen is currently an important field in energy development. Abstract : Electrolyzing water technology to prepare high-purity hydrogen is currently an important field in energy development. However, the preparation of efficient, stable, and inexpensive hydrogen production technology from electrolyzed water is a major problem in hydrogen energy production. The key technology for hydrogen production from water electrolysis is to prepare highly efficient catalytic, stable and durable electrodes, which are used to reduce the overpotential of the hydrogen evolution reaction and the oxygen evolution reaction of electrolyzed water. The main strategies for preparing catalytic electrodes include: (i) choosing cheap, large specific surface area and stable base materials, (ii) modulating the intrinsic activity of the catalytic material through elemental doping and lattice changes, and (iii) adjusting the morphology and structure to increase the catalytic activity. Based on these findings, herein, we review the recent work in the field of hydrogen production by water electrolysis, introduce the preparation of catalytic electrodes based on nickel foam, carbon cloth and new flexible materials, and summarize the catalytic performance of metal oxides, phosphides, sulfides and nitrides in the hydrogen evolution and oxygen evolution reactions. Secondly, parameters such as the overpotential, Tafel slope, active site, turnover frequency, and stability are used as indicators to measure the performance of catalytic electrode materials. Finally, taking the material cost of the catalytic electrode as a reference, the successful preparations are comprehensively compared. The overall aim is to shed some light on the exploration of high-efficiency and economical electrodes in energy chemistry and also demonstrate that there is still room for discovering new combinations of electrodes including base materials, composition lattice changes and morphologies.